Six-element high-entropy oxide glass with equal molar ratio as well as preparation method and application of six-element high-entropy oxide glass
By mixing six oxides in equal molar ratios and adopting special preparation methods, the preparation problem of six-member high-entropy oxide glass was successfully broken through, and an equimolar six-member high-entropy oxide glass with ultra-high refractive index and excellent mechanical properties was prepared, solving the problem that it is difficult to prepare six-member high-entropy oxide glass in traditional methods.
Patent Information
- Application Number
- CN202311350104.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
AI Technical Summary
There are currently no reports of six-membered high-entropy oxide glasses, especially six-membered high-entropy oxide glasses that meet the principle of component equimolar ratio. It is difficult for traditional methods to prepare six oxide vitrification samples without network formations.
Six oxides such as lanthanum trioxide, aluminum trioxide, titanium dioxide, niobium pentoxide, zirconium dioxide, and tantalum pentoxide were prepared by ball milling, drying, prefixing, container-free melt-solidification treatment and annealing.
Equimolar six-membered high-entropy oxide glass with ultra-high refractive index, excellent optical and mechanical properties was successfully prepared. The application window was wide and its performance was better than that of the existing high-entropy oxide glass system.
Smart Images

Figure CN119841550A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of oxide glass materials, and specifically relates to a high-performance high-entropy oxide glass made of six oxides, namely, lanthanum trioxide, aluminum trioxide, titanium dioxide, niobium pentoxide, zirconium dioxide and tantalum pentoxide, in an atomic equimolar ratio, and a preparation method and application thereof. Background Art
[0002] Glass is an amorphous substance and a typical amorphous solid, showing the structural characteristics of short-range order and long-range disorder. The application fields of glass are diverse, and the products of glass are ever-changing. At present, most of the various types of glass products contain network formers such as SiO2, B2O3, P2O5, etc., which form coordination polyhedrons with other components in the glass and become the basic structural units of the glass network. By regulating the components and structure of the glass, the performance of existing glasses containing network formers can be improved. However, for certain specific properties, such as ultra-high refractive index and mechanical properties, due to the constraints of the characteristics of the SiO2 component itself and the Si-O polyhedral network structure, the concentration of other components that can be doped is low, and the adjustable space of the structure such as coordination number and stacking density is limited, making it difficult to further improve the performance. The emergence of new non-network former glass fills this gap. Since it does not contain network formers such as SiO2, B2O3, and P2O5, non-network former glass has a special composition and structure compared to traditional glass, breaking the limitations of traditional glass containing network formers in ultra-high refractive index, ultra-high mechanical properties, etc. The performance optimization of traditional glass often focuses on the replacement and doping of some components. The direct elimination of network formers in the system is a bold attempt to regulate the composition and structure of glass, but it is still a conventional method of performance regulation. In recent years, the emergence of high-entropy materials has provided a new idea for the regulation of glass performance.
[0003] High entropy materials are a new type of material system that has attracted much attention in recent years. They are usually composed of five or more components in equimolar or nearly equimolar ratios. The emergence of high entropy materials has overturned the concept of single-component-based traditional material design. The increase in the number of components has greatly enriched the space for material composition design and structure-performance regulation, and has received widespread attention in the fields of metals, ceramics, and intermetallic compounds. Due to the large number of components, high entropy materials have unique effects, including high entropy effects in thermodynamics, lattice distortion effects in structure, hysteresis diffusion effects in kinetics, and cocktail effects in performance. Compared with traditional materials, high entropy materials have shown unique advantages in mechanical, physical, and chemical properties, and have become one of the important research hotspots in the field of materials at home and abroad.
[0004] The research on high entropy oxide glass is currently in its initial stage. It is a new topic in the field of high entropy amorphous materials. Existing research mainly focuses on high entropy non-network-forming glass. In the field of alloys and ceramics, since the requirements for cations at specific crystal sites are relatively broad, it is relatively easy to prepare high entropy samples. The difference between glass and alloys or ceramics lies mainly in the uncertainty of glass formation. The amorphous forming ability of glass is still a major problem in the field. The difference in component design is mainly reflected in "no rules to follow". It is often difficult to prepare glass samples by replacing only one adjacent element in the same period or the same main group in the same system glass. Therefore, the principle of equimolar ratio of components of high entropy crystal materials is quite difficult for high entropy glass. At present, high entropy oxide glass that meets the principle of equimolar ratio of components has only been successfully prepared by Professor Qi Xiwei and others. They disclosed a five-element high entropy oxide glass with equimolar ratio in patent CN108821571B.
[0005] So far, there has been no report on six-element high entropy oxide glass, especially six-element high entropy oxide glass that meets the principle of equimolar ratio of components. In addition, the six oxides of lanthanum trioxide, aluminum trioxide, titanium dioxide, niobium pentoxide, zirconium dioxide, and tantalum pentoxide do not contain any network formers, and it is difficult to vitrify the samples by traditional methods. So far, no relevant reports on equimolar high entropy oxide glass prepared by this system have been retrieved. Summary of the invention
[0006] In view of the problems existing in the prior art and in order to further expand and enrich the research field of high entropy oxide glass, the present invention provides an equimolar ratio hexavalent high entropy oxide glass and a preparation method and application thereof.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A six-element high entropy oxide glass with equal molar ratio, comprising six oxides: lanthanum trioxide (La2O3), aluminum trioxide (Al2O3), titanium dioxide (TiO2), niobium pentoxide (Nb2O5), zirconium dioxide (ZrO2), and tantalum pentoxide (Ta2O5), wherein La 3+ 、Al 3+ 、Ti 4+ , Nb 5+ 、Zr 4+ 、 5+ Mix in equal molar ratio, i.e. La 3+ Ion 1 / 6, Al 3+ Ion 1 / 6, Ti 4+ Ion 1 / 6, Nb 5+ Ion 1 / 6, Zr 4+ Ion 1 / 6, Ta 5+Ion 1 / 6.
[0009] A method for preparing an equimolar ratio hexavalent high entropy oxide glass comprises the following steps:
[0010] (1) Six oxide powders of lanthanum trioxide, aluminum trioxide, titanium dioxide, niobium pentoxide, zirconium dioxide, and tantalum pentoxide are accurately weighed according to a stoichiometric ratio of equimolar atomic ratio, anhydrous ethanol is added, and the mixture is ball-milled on a planetary ball mill for 8 to 10 hours until the powders are uniformly mixed;
[0011] (2) The powder after ball milling is fully dried and then sieved, the mesh number of the sieve is greater than 100 mesh, and the sieved powder is placed in a muffle furnace for pre-calcination at a temperature of 700 to 900° C. for a holding time of 3 to 6 hours;
[0012] (3) Pressing the pre-fired raw material mixture into a glass raw material block, and performing a containerless melting-solidification process: The obtained glass raw material block is stably suspended in the air, heated to a molten state, and then cooled to obtain a glass sample;
[0013] (4) In order to eliminate the thermal stress generated inside the glass due to the temperature difference, the glass sample after the containerless melting-solidification treatment is placed in an annealing furnace for annealing, and finally the equimolar ratio hexavalent high entropy oxide glass is obtained.
[0014] Furthermore, the drying temperature in step (2) is 70-150° C., and the drying time is 1-2 hours.
[0015] Furthermore, the pressure of pressing the glass raw material block in step (3) is 5 to 20 MPa.
[0016] Furthermore, the suspension method in step (3) is pneumatic suspension, and the gas used for suspension is oxygen.
[0017] Furthermore, the heating method in step (3) is CO2 laser heating.
[0018] Furthermore, the melt temperature of the molten state in step (3) is 2000-3300°C.
[0019] Furthermore, the cooling rate of step (3) is 180 to 300 K / s.
[0020] Furthermore, the annealing temperature in step (4) is 400-700° C., the annealing time is 1-5 hours, and then the power is turned off and the furnace is cooled to room temperature.
[0021] An application of an equimolar ratio hexavalent high entropy oxide glass, the application comprising using the equimolar ratio hexavalent high entropy oxide glass to manufacture AR / VR glasses, electronic product covers, precision instruments, touch panels, optical lenses or smart devices, etc.
[0022] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0023] (1) The present invention discloses and prepares six-component high-entropy oxide glass with equal molar ratio for the first time, breaking through the current limitation that the number of components of high-entropy oxide glass can only be five at most, thus greatly broadening and enriching the research in the field of high-entropy oxide glass.
[0024] (2) The equimolar ratio hexavalent high entropy oxide glass prepared by the present invention has excellent comprehensive performance, ultra-high refractive index and excellent optical and mechanical properties, and an extremely wide application window. The refractive index at a wavelength of 587.6nm is as high as 2.21, and the maximum transmittance of visible light in the range of 400nm to 800nm can reach 79%. The hardness is as high as 10.74GPa, and the Young's modulus is as high as 162.5GPa. The comprehensive performance is better than other high entropy oxide glass systems reported in the current literature.
[0025] (3) The method for preparing the equimolar ratio hexavalent high entropy oxide glass of the present invention is characterized by easy operation, strong practicability and easy promotion and application. The container-free melting-solidification process can avoid the contact between the melt and the container wall, inhibit heterogeneous nucleation, and enable the melt to obtain a deep undercooling, thereby avoiding the problem of easy crystallization by the high-temperature solid phase method and facilitating the formation of glass.
[0026] (4) The equimolar ratio hexavalent high entropy oxide glass of the present invention has great application potential in multiple fields, including AR / VR glasses, electronic product covers, precision instruments, touch panels, optical lenses and smart devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD spectrum of the equimolar ratio hexavalent high entropy oxide glass prepared by the present invention;
[0028] Figure 2 The wavelength-refractive index spectrum of the equimolar ratio hexavalent high entropy oxide glass prepared by the present invention, the refractive index reaches 2.21;
[0029] Figure 3 This is a test depth-hardness curve of the equimolar ratio hexavalent high entropy oxide glass prepared by the present invention, and the hardness reaches 10.74 GPa;
[0030] Figure 4 The test depth-Young's modulus curve of the equimolar ratio hexavalent high entropy oxide glass prepared by the present invention, the Young's modulus reaches 162.5 GPa;
[0031] Figure 5 This is a physical picture of the equimolar ratio hexavalent high entropy oxide glass prepared by the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0033] Example 1
[0034] The present embodiment provides a six-element high entropy oxide glass with an equal molar ratio, including six oxides: lanthanum trioxide (La2O3), aluminum trioxide (Al2O3), titanium dioxide (TiO2), niobium pentoxide (Nb2O5), zirconium dioxide (ZrO2), and tantalum pentoxide (Ta2O5). 3+ 、Al 3+ 、Ti 4+ , Nb 5+ 、Zr 4+ 、 5+ Mix in equal molar ratio, i.e. La 3+ Ion 1 / 6, Al 3+ Ion 1 / 6, Ti 4+ Ion 1 / 6, Nb 5+ Ion 1 / 6, Zr 4+ Ion 1 / 6, Ta 5+ Ion 1 / 6.
[0035] The preparation method comprises the following steps:
[0036] (1) La2O3, Al2O3, TiO2, Nb2O5, ZrO2, and Ta2O5 powders (all with a purity of 99.99%) were accurately weighed according to the stoichiometric ratio of atomic equimolar ratio, poured into a ball mill, and ball milling beads and anhydrous ethanol that covered the raw material powders were added. The mixture was placed in a planetary ball mill and milled for 10 h until it was uniformly mixed.
[0037] (2) The mixed raw material powder is placed in a forced air drying oven at 100°C for 2 hours, then passed through a 150-mesh sieve, and the sieved powder is placed in a muffle furnace for pre-calcination at 700°C for 4 hours. After cooling, it is pressed into blocks using a powder tablet press at a pressure of 10 MPa.
[0038] (3) Select a small piece of appropriate size and place it on the nozzle of the laser-heated pneumatic suspension equipment. Control the CO2 laser power and the flow rate of the gas (oxygen) used for suspension. Heat it to a molten state with a melt temperature of 2700°C and stably suspend it on the nozzle for 50 seconds. Then adjust the laser power to solidify the melt at a cooling rate of 240 K / s.
[0039] (4) placing the melt-solidified glass sample in an annealing furnace and annealing at 500° C. for 2 h, then turning off the power and cooling the furnace to room temperature to obtain the equimolar ratio hexavalent high entropy oxide glass, such as Figure 5 As shown, the words on the paper can be clearly seen through the glass.
[0040] Structural characterization and performance testing of the molar ratio hexavalent high entropy oxide glass described in this example:
[0041] (1) The structure of the equimolar ratio hexavalent high entropy oxide glass was characterized using a Smartlab 9 X-ray diffractometer manufactured by Japan Co., Ltd. Figure 1 The XRD spectrum shows broad diffraction peaks that are unique to amorphous materials, indicating that the prepared sample is indeed amorphous glass.
[0042] (2) The refractive index of the equimolar ratio hexavalent high entropy oxide glass was tested using an SE850 DUV ellipsometer from German company SENTECH. Figure 2 As shown. The refractive index n at 587.6nm d As high as 2.21, it is an ultra-high refractive index glass with a very wide application window.
[0043] (3) The hardness and Young's modulus of the equimolar ratio hexavalent high entropy oxide glass were tested using an XP-TP263 nanoindenter from MTS, USA, as follows: Figure 3 and Figure 4 As shown. The hardness is as high as 10.74GPa and the Young's modulus is as high as 162.5GPa, which has excellent mechanical properties.
[0044] Comparative Example 1
[0045] Except that the gas used for suspension in step (3) of the preparation method described in Example 1 was set to argon, other conditions were exactly the same as in Example 1, and the obtained sample was non-transparent.
[0046] Comparative Example 2
[0047] Except that the heating to the melt temperature in step (3) of the preparation method described in Example 1 was set to 1900° C., other conditions were exactly the same as in Example 1, and the obtained sample was non-transparent.
[0048] Comparative Example 3
[0049] Except that the cooling and solidification rate in step (3) of the preparation method described in Example 1 was set to 170K / s, other conditions were exactly the same as in Example 1, and the obtained sample was non-transparent.
[0050] The present invention obtains a hexameric equimolar high-entropy oxide glass having an ultra-high refractive index, excellent optical and mechanical properties, and an extremely broad application window by selecting appropriate oxides and controlling corresponding preparation methods.
[0051] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.
[0052] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. An equimolar ratio hexavalent high entropy oxide glass, characterized in that: The components of the equimolar ratio hexavalent high entropy oxide glass are lanthanum trioxide, aluminum trioxide, titanium dioxide, niobium pentoxide, zirconium dioxide, and tantalum pentoxide. 3+ 、Al 3+ 、Ti 4+ , Nb 5+ 、Zr 4+ 、 5+ Mix in equal molar ratio, i.e. La 3+ Ion 1 / 6, Al 3+ Ion 1 / 6, Ti 4+ Ion 1 / 6, Nb 5+ Ion 1 / 6, Zr 4+ Ion 1 / 6, Ta 5+ Ion 1 / 6.
2. A method for preparing a six-element high entropy oxide glass with an equal molar ratio, the preparation method comprising the following steps: (1) accurately weighing six oxide powders of lanthanum trioxide, aluminum trioxide, titanium dioxide, niobium pentoxide, zirconium dioxide, and tantalum pentoxide according to a stoichiometric ratio of equimolar atomic ratio, adding anhydrous ethanol and ball milling for 8 to 10 hours until the powders are uniformly mixed; (2) The ball-milled powder is fully dried and then sieved, the mesh number of the sieve is greater than 100 mesh, and the sieved powder is pre-calcined at a temperature of 700 to 900° C. for a holding time of 3 to 6 hours; (3) pressing the pre-fired raw material mixture into a glass raw material block and performing a containerless melting-solidification process; (4) The glass sample after the containerless melting-solidification treatment is placed in an annealing furnace for annealing to obtain an equimolar ratio hexavalent high entropy oxide glass.
3. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 2, characterized in that: In step (2), the drying temperature is 70 to 150° C. and the drying time is 1 to 2 hours.
4. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 2, characterized in that: In step (3), the pressure for pressing the glass raw material block is 5 to 20 MPa.
5. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 2, characterized in that: The containerless melting-solidification process is specifically as follows: The obtained glass raw material block is stably suspended in the air, heated to a molten state, and then cooled to obtain a glass sample.
6. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 5, characterized in that: The suspension method is pneumatic suspension, and the gas used for suspension is oxygen.
7. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 5, characterized in that: The heating method is CO2 laser heating.
8. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 5, characterized in that: The temperature of the melt heated to a molten state is 2000-3300° C.; the cooling rate of the melt is 180-300 K / s.
9. The method for preparing the equimolar ratio hexavalent high entropy oxide glass according to claim 2, characterized in that: The temperature of the annealing treatment in step (4) is 400-700° C., the annealing time is 1-5 hours, and then the power is turned off and the furnace is cooled to room temperature.
10. An application of the equimolar ratio hexavalent high entropy oxide glass according to claim 1, characterized in that: The application includes using the equimolar ratio hexavalent high entropy oxide glass to manufacture AR / VR glasses, electronic product covers, precision instruments, touch panels, optical lenses or smart devices.
Citation Information
Patent Citations
A high-entropy oxide amorphous material and its preparation method
CN108821571B